Prediction of planted seedling survival of five Mediterranean species based on initial seedling morphology - Tsakaldimi, Marianthi; Ganatsas, Petros; JACOBS, DOUGLASS F (New Forests, 2012)
Field performance can be predicted by evaluating nursery stock quality, but optimal morphological variables for use in these assessments may vary by species especially under dry Mediterranean conditions. Our objective was to identify initial seedling morphological characteristics that successfully predict ﬁeld performance of ﬁve Mediterranean species (Pinus halepensis, Quercus ilex, Quercus coccifera, Ceratonia silqua and Pistacia lentiscus). Container seedling morphology was evaluated following the nursery phase, and then seedlings were outplanted in the ﬁeld where ﬁeld survival was monitored for two successive years. Results indicate that survival can successfully be predicted from seedling initial morphological characteristics for all these species, yet not all the initial characteristics were good predictors. Survival of P. halepensis and Pist. lentiscus seedlings was positively correlated to initial seedling root-collar diameter, total dry weight and Dickson’s quality index, and can be reliably predicted by these variables. In contrast, seedling ﬁeld survival of the two Mediterranean evergreen oak species was correlated with few initial morphological attributes; initial diameter provided an accurate index to predict second-year outplanting survival for both species while height/diameter was a good survival predictor for Q. coccifera seedlings. For C. siliqua seedlings, seedlings with larger initial diameter and total biomass survive better in the ﬁeld. Thus, diameter was the common variable that accurately predicted survival for all species, which should be [5 mm for P. halepensis seedlings and[7 mm for the remaining species.
Keywords: Field performance; morphology; outplanting; Prediction models; seedling quality